2013
DOI: 10.1055/s-0033-1345589
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Medicine Approaches to Male Infertility

Abstract: Male factor is a common cause of infertility and the male partner must be systematically evaluated in the workup of every infertile couple. Various Eastern medical strategies have been tried with variable success. This article describes the clinical effects of Eastern medicine approaches including acupuncture, Chinese herbal medicine, massage, yoga, tai chi, and qi gong, which could improve the sperm parameters and motility, genital inflammatory conditions, as well as immune system disorders, sexual dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 62 publications
0
12
0
2
Order By: Relevance
“…Therefore, alternative herbal remedies with a long history of use have become a novel option, gradually attracting attention. Historical Eastern medical approaches, especially traditional Chinese medicine (TCM), have had beneficial effects on male infertility (Hu et al, 2013). TCM has been used in the clinical context for thousands of years, and is a successful option for many infertile Chinese male patients throughout the country, despite the lack of scientific evidence to support its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative herbal remedies with a long history of use have become a novel option, gradually attracting attention. Historical Eastern medical approaches, especially traditional Chinese medicine (TCM), have had beneficial effects on male infertility (Hu et al, 2013). TCM has been used in the clinical context for thousands of years, and is a successful option for many infertile Chinese male patients throughout the country, despite the lack of scientific evidence to support its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of infertile men with oligozoospermia was high compared to individuals with obstructive azoospermia (p <0.05). These abnormality parameters affect 50 % of men with infertility, being a more common alteration in oligoastenoteratozoospermia 14 . As the genetic abnormalities found seem to be classified as less important when compared to an obstructive azoospermia (p <0.05), but it is relevant data.…”
Section: Resultsmentioning
confidence: 99%
“…People with infertility problems often seek complementary and alternative medicine [4]. Several studies have shown that many sufferers have used some form of herbal medicine, such as dang gui, maca, or ginseng, in order to try to improve their fertility, libido, and sexual performance [4][5][6][7][8][9][10][11]. Ginseng is the root of the Panax plant.…”
Section: Introductionmentioning
confidence: 99%